Knowledge Communities in Teacher Education Sustaining Collaborative Work - Craig, Cheryl J.; Curtis, Gayle A.; Kelley, Michaelann; Martindell, P. Tim; Pérez, M. Michael (Palgrave Studies on Leadership and Learning in Teacher Education, 2020)
XXV, 252 p. 9 illus., 5 illus. in color.